Surface tension effects on flow dynamics and alveolar mechanics in the acinar region of human lung - Isabella Francis; Suvash C. Saha (Heliyon, 2022)
Background: Computational fluid dynamics (CFD) simulations, in-vitro setups, and experimental ex-vivo approaches have been applied to numerous alveolar geometries over the past years. They aimed to study and examine airflow patterns, particle transport, particle propagation depth, particle residence times, and particle-alveolar wall deposition fractions. These studies are imperative to both pharmaceutical and toxicological studies, especially nowadays with the escalation of the menacing COVID-19 virus. However, most of these studies ignored the surfactant layer that covers the alveoli and the effect of the air-surfactant surface tension on flow dynamics and air-alveolar surface mechanics. Methods: The present study employs a realistic human breathing profile of 4.75s for one complete breathing cycle to emphasize the importance of the surfactant layer by numerically comparing airflow phenomena between a surfactant-enriched and surfactant-deficient model. The acinar model exhibits physiologically accurate alveolar and duct dimensions extending from lung generations 18 to 23. Airflow patterns in the surfactant-enriched model support previous findings that the recirculation of the flow is affected by its propagation depth. Proximal lung generations experience dominant recirculating flow while farther generations in the distal alveolar region exhibit dominant radial flows. In the surfactant-enriched model, surface tension values alternate during inhalation and exhalation, with values increasing to 25 mN/m at the inhalation and decreasing to 1 mN/m at the end of the exhalation. In the surfactant-deficient model, only water coats the alveolar walls with a high surface tension value of 70 mN/m. Results: Results showed that surfactant deficiency in the alveoli adversely alters airflow behavior and generates unsteady chaotic breathing through the production of vorticities, accompanied by higher vorticity magnitudes (100% increase at the end of exhalation) and higher velocity magnitudes (8.69% increase during inhalation and 11.9% increase during exhalation). In addition, high air-water surface tension in the surfactant-deficient case was found to induce higher shear stress values (by around a factor of 10) on the alveolar walls than that of the surfactant-enriched case. Conclusion: Overall, it was concluded that the presence of the surfactant improves respiratory mechanics and allows for smooth breathing and normal respiration.